Fight against Oblivion and Signal Hope. Memory policies and Teaching practices in a school from Mar del Plata (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
During 2017, a group of teachers from the School of Secondary Education No. 1 in the city of Mar del Plata began to work on the implementation of a project aimed at recovering the memory of the institution linked to the recent past of State terrorism in the city. This project pursued the objective of declaring the school a Historic Site ‘for the memory of collective dreams’, and the actors narrate their vision of the events, from a political perspective, militant and autobiographical trajectories on school. This article describes and analyses the teaching practices carried out during the launch of this memory undertaking in EES No. 1. We hope this exercise will contribute to reflection on the treatment of the recent past in the educational field and its interrelation with the memory policies that emerge from social struggles for its meaning.
Keywords: teaching practices, recent past, memory entrepreneurship, historic site